593 Odds of Receiving Sleep Diagnoses in Common Pediatric Chronic Medical Conditions. (3rd May 2021) - Munoz, Tomas; Patel, Palakkumar; Adavadkar, Pranshu
Abstract: Introduction: Sleep disorders (SD) are under-diagnosed in the general pediatric population. Children with chronic medical conditions (CMC) tend to have a higher prevalence rate of SD; however, the studies about the rates of diagnosis of SD are limited. We examined the odds of receiving SD diagnoses in children with various CMC and hypothesized that if this likelihood is established, screening tools can be developed to increase the rates of diagnoses and improve clinical outcomes. Methods: Chi-square test and regression analysis were used to test the association between SD and CMC based on ICD-9 and -10 diagnosis codes retrieved from the Medicaid claims submitted for children (0 to 18 years) enrolled in the Centers for Medicare and Medicaid Services-funded Coordinated Health Care for Complex Kids (CHECK) project, at an urban, public tertiary care hospital. Children without a CMC were excluded. Results: Among 16, 609 children with CMC (mean [SD] age of 9.1 [5.3] years; 56.4% male; 77% with multiple CMC), 14.1% received a diagnosis of SD. Compared to the cohort without a particular CMC, children with attention deficit hyperactivity disorder (ADHD), obesity, developmental disorder, or asthma had following odds of receiving sleep diagnosis respectively (odds ratio (OR) [Confidence Interval]): insomnia (6.9 [5–9.5]; 2.4 [1.7–3.2]; 1.6 [1.2–2.3]; 0.7 [0.5–1]), circadian rhythm disorders (6.1[2.7–13.7]; 2.8 [1.3–2.6]; 3.0 [1.4–6.4]; 0.5* [0.2–1.1]), hypersomnia (2.9 [1.0–8.6]; 7.8 [3–20.2], 0.9* [0.3–2.6], 0.8* [0.3–2.2]), and sleep-related movement disorder (1.9* [0.9–4.3]; 4.4 [2.5–7.8]; 2.2 [1.2–3.9]; 0.6*[0.3–1.1]). (*=p value <0.05). Conclusion: Odds of receiving sleep diagnoses vary across CMC. Among others, strong associations between obesity-hypersomnia and ADHD-insomnia were noted. This information may help clinicians implement appropriate screening interventions to improve early SD detection and management. Further studies to examine these associations are necessary. Support (if any):